Potential uses of human salivary protein and peptide analysis in the diagnosis of disease - Kawas, S.A.; Rahim, Z.H.A.; Ferguson, D.B. (2012)
Saliva is an important body fluid containing a complex mixture of proteins, peptides and other substances. These are not only important in maintaining the health of the oral cavity but also may yield information about oral and systemic disease. Comprehensive analysis and identification of the proteomic content of human saliva may contribute to the understanding of oral pathophysiology and provide a foundation for the recognition of potential biomarkers of human disease. The collection of saliva samples is non-invasive, safe, and inexpensive. It seems likely that testing methods can be developed which can be used in general medical or dental practice. However, it is important to realize that the collection of saliva must be carefully controlled. In this paper we review the progress in the analysis of the human salivary proteome and summarise the diagnostic possibilities that have been explored. The precautions in collecting saliva, and some of the factors which would have to be considered if a diagnostic test were to be generally adopted are discussed.